Should ECNs be SOES-able? - Bruce Mizrach; Yijie Zhang (Rutgers University, Department of Economics, 2000)
This paper documents the significant role of ECNs in forming the inside market in NASDAQ securities. We argue that the ECNs need to be exposed to market orders through the SOES system.
Keywords: G1; G14; 330; ECN; microstructure; NASDAQ; SOES